Digital Engagement Practices in Mobile Trading: The Impact of Color and Swiping to Trade on Investor Decisions - Grant, Stephanie M.; Hobson, Jessen L.; Sinha, Roshan K. (Management Science, 2024)
As coined by the SEC, Digital Engagement Practices (DEPs) are visual cues and design features to engage investors on mobile trading platforms. With the rise of mobile stock trading, regulators and other capital market participants are concerned that these DEPs may cause retail investors to trade in ways they otherwise would not. Using an experiment, we examine the impact of two common DEPs in mobile trading platforms—color (i.e., the use of green or red to indicate performance) and allowing investors to swipe versus click and confirm to execute trades. Drawing from prior research, we predict that the color associated with firm information will interact with how investors execute their trades to affect investment decisions. Consistent with expectations, results show that investors make the largest investment in a firm when they swipe to trade and firm information is colored green, relative to when they click and confirm to trade or firm information is colored red, holding firm economics constant. Swiping to trade causes investors to focus relatively more on the upside of investing, but only when firm information is colored green and not when it is colored red. The color red leads to a muted effect of swiping to trade as investors experience more negative affect and focus relatively more on the downside of investing. Our study answers calls from regulators and academics to examine the effects of technology on information evaluation in investment decisions, and has important practical implications for investors. This paper was accepted by Ranjani Krishnan, accounting. Supplemental Material: The data is available at https://doi.org/10.1287/mnsc.2023.00379 .